High ductility bulk nanostructured Al–Mg binary alloy processed by equal channel angular pressing and inter-pass annealing. (August 2015) - Zha, Min; Li, Yanjun; Mathiesen, Ragnvald H.; Bjørge, Ruben; Roven, Hans J.
Abstract : Bulk nanostructured (NS) metallic materials usually have high strength but extremely low ductility. In this study, we successfully prepared a bulk NS binary Al–7 Mg alloy possessing both high strength and high uniform ductility, approaching ∼600 MPa and ∼14%, respectively, by utilizing room temperature equal channel angular pressing (ECAP) combined with inter-pass annealing. The mechanism that governs the high ductility in the alloy and especially the role of the high Mg solute concentration was explored in terms of microstructure analysis.